Factors that encourage students' involvement in entrepreneurship: A study at UiTM Shah Alam / Zahidah Ahmad - Ahmad, Zahidah (Academy of Contemporary Islamic Studies, 2018)
It has always been the awareness of our government to encourage entrepreneurship and new venture in business as a purpose to improve economic growth for the nation and creating jobs to help solving the problem of unemployment. The purpose of this study is to identify the factors that encourage students' involvement in entrepreneurship among students in University Technology MARA (UiTM) Shah Alam. This study focuses on five main factors which is academic background, family background, entrepreneurial skills, personal attitude and support system. A set of questionnaires were distributed to students in UiTM Shah Alam who are the entrepreneurs. The questionnaires consist of four sections which is for Section ADemographic, Section B- Background of Entrepreneurship, Section C- Factors that Encourage Students' Involvement in Entrepreneurship and Section D-Opinion on the efforts that should be taken by UiTM in order to attract students venture into entrepreneurship. The data collected through the questionnaires were analyzed using Statistical Product and Service Solutions (SPSS) software 20.0. First result shows that the main factor that encourages students' involvement in entrepreneurship is factor on personal attitude. Second result shows the efforts that should be taken by university to attract more students involve with entrepreneurship is by organizing entrepreneurship program, giving financial support; provide facilities, reducing or eliminating fees and giving appreciation.